(untitled) (NAU Journal of Technology and Vocational Education, 2026)
The study ascertained Application of Open Educational Resources and efficacy of teaching Business Education courses in tertiary institutions. The study was carried out in Rivers State tertiary institutions offering Business Education programme. Three specific objectives, research questions and null hypotheses guided the study. The study adopted correlational research design. The population of the study was 105 Business Educators from 6 tertiary institutions in Rivers State. Based on the small population size, the entire population was studied. Two sets of self-structured questionnaire titled “Application of Open Educational Resources (AOER) and Efficacy of teaching Business Education courses ETBEC) were used for data collection. Pearson’s Product Moment Correlation (PPMC) was used to answer the research question and test the null hypotheses at 0.05 level of significance. Findings from the study revealed, that there is a positive relationship between the application of Coursera, edX and Khan open educational resources and the efficacy of teaching of Business Education courses. The result of the study also showed that the calculated r-value for the three hypotheses were greater than the table value of 0.179. Therefore, the null hypothesis which states no significant relationship between OLRs and the efficacy of teaching of Business Education courses is rejected, meaning that there is a “significant relationship between OLRs and the efficacy of teaching Business Education courses. Conclusively, open learning resources have revolutionized the educational landscape and helped Business Educators to deliver content effectively, engage students meaningfully, and achieve desired learning outcomes. It has also helped in classroom interaction, instructional innovation, and assessment effectiveness. It is recommended among others that there should be emulsification of teaching material and resources to enhance the efficacy of teaching, especially Business Education courses.